Rekomendasi Pengelolaan Sampah Pada Ekowisata Mangrove Wonorejo Surabaya - Rachmadiarazaq; Siti Adelita Raif Khadijah; Alhilal Furqan (JURNAL KEPARIWISATAAN, 2023)
Wonorejo Mangrove Ecotourism Surabaya is a tourist destination based on mangrove forests in the east coast of Surabaya City. On weekends, Wonorejo Mangrove Ecotourism Surabaya can attract 300 to 350 visitors. However, the tourism activities carried out by the visitors will have impacts, either positive or negative related to the environment, economy and social aspects. Judging from the concept of sustainable tourism, good waste management is an important aspect that must be considered for the sustainability of this destination. This study aimed to identify and provide recommendations for waste management that has been carried out at Wonorejo Mangrove Ecotourism Surabaya.  This research used  a qualitative descriptive analysis method. Ekowisata Mangrove Wonorejo Surabaya has a management system for organic and inorganic waste that has been implemented. However, Wonorejo Mangrove Ecotourism Surabaya still has to provide and improve facilities and infrastructure for organic and inorganic waste management.